The Role of Arbitrators in Settlement of Land Acquisition Cases according to Law Number 30 of 1999 - Rusdiannor Rusdiannor; Taufiqurachman Taufiqurachman (JOURNAL of LEGAL RESEARCH, 2021)
Resolution of conflicts through civil channels is particularly stated in Law Number 30 of 1999 concerning Arbitration, which governs the arbitration process. According to the findings of the investigation, the matter was decided by the Amuntai District Court on July 14, 2014, by the issuance of decision letter No. 08/PDT.G/2011. The research method that was employed was a normative research method that took a legislative approach to the problem. Document studies and interviews are utilized to gather information, which is then processed. While qualitative analysis is the method of data analysis employed here. According to the findings of the study, it can be inferred that the conflict has not been resolved, but is still in the midst of being resolved.